Problems in specification and interpretation of central bank reaction functions - Dean, James W. (Economic & Social Studies, 1974)
The last decade, beginning with the work of Teigen, has seen widespread recognition of the need to 'endogenise' the supply of money in order to obtain consistent (i.e. asymptotically unbiased) estimates of the parameters in the money-demand1 and other equations of an econometric system. Most such models, however, assume the central bank's policy-instrument (typically, commercial banks' reserves or the monetary base) to be exogenous.
Keywords: Central Bank